Rhetorics of saving–investment correlations and the international mobility of capital: A survey. Issue 5 (3rd July 2016) - Singh, Tarlok
ABSTRACT: This study surveys the literature on saving–investment (SI) correlations and international mobility of capital (IMC) generated over more than three decades since the 1980s. Several studies have shown the presence of paradoxically high SI correlations for the developed countries with observed high IMC, and low SI correlations for the developing countries with observed low IMC. The studies accounting for structural breaks in model parameters provide dominant support for the decrease in SI correlations and increase in IMC after the switch from fixed to flexible exchange rate regime and the removal of policy restrictions on capital flows. The intertemporal optimisation approach to current account and the open-economy growth and dynamic stochastic general equilibrium models mainly provide theoretical predictions and suggest that it is possible to find high SI correlations in the wake of high IMC. The increases in international capital flows have been the natural corollary of the growth of international trade in goods and services and increases in foreign direct investment flows. It is these factors, rather than international trade in capital market securities (bonds and equities) driven by the diversification benefits of financial portfolios per se, that have been the key levers of international financial flows.